Influence of Work Environment and Organizational Culture On Employee Performance As Intervening Variables: Pengaruh Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Karyawan Sebagai Variabel Intervening - Setia Karmila Giawa, Wita (LPPM UPMI, 2024)
Work environment is the overall conditions and factors that influence employee experiences in the workplace. It includes various elements that can affect comfort, productivity, and job satisfaction. This study aims to explore the influence of work environment and organizational characteristics on employee performance as intervening variables. The method used is a qualitative approach through in-depth interviews and focus group discussions with employees from various levels in several companies. The data obtained were analyzed using systematic analysis to identify patterns and relationships that emerge from employee experiences. The results of the study indicate that a supportive work environment, including adequate facilities and a collaborative atmosphere, as well as clear organizational characteristics, such as strong values ​​and missions, contribute to improved employee performance. The results of the study indicate that the work environment has a positive and significant effect on job satisfaction and organizational commitment. Employee performance serves as a bridge connecting the two factors, where employees feel more motivated and engaged when the environment and organizational characteristics are positive. These findings provide important insights for management in designing strategies to improve performance through the development of a better work environment and organizational characteristics.